An internationally competitive economy: A comparison of Poland and the Visegrad Group Countries in the post-accession period - Edward Molendowski (Comparative Economic Research. Central and Eastern Europe, 2017)
This article presents the results of an analysis comparing the competitive position of Poland and other countries of the Visegrad Group (V4) in the post-accession period (2004-2015). The assumption is that among the V4 countries, Poland has joined those countries where the diverse effects of EU membership are clearly visible. In the study, analysis was applied to secondary data pertaining to pillars of economic competitiveness, as determined by the "Global Competitiveness Reports" prepared by the World Economic Forum. The article ends with a list of vital conclusions based on the presented analysis.
Keywords: E2; E6; F4; F5; 330; international economic competitiveness; effects of EU membership; Poland; Visegrad Group; V4